Mandatory due diligence for 'conflict minerals' and illegally logged timber: Emergence and cascade of a new norm on foreign accountability. Issue 4 (November 2016) - Partzsch, Lena; Vlaskamp, Martijn C.
Highlights: Industries increasingly disclose conditions of extraction abroad due to a new foreign accountability norm. The emergence of the norm is the result of strategic framing by moral activists, such as Global Witness and the Enough Project. Marketing of "fair business" entrepreneurs plays an important role during the current phase of norm cascade. Abstract: The European Union, the United States, and a number of other state actors have adopted policies obliging companies to conduct supply chain due diligence regarding the import of natural resources. While several authors have analyzed the motives of these measures individually, this article provides a broader explanation for their diffusion. In empirical terms, it focuses on 'conflict minerals' and illegally logged timber. Building on the classical norm life cycle, the article's argument is threefold. Firstly, it argues that these mandatory due diligence policies are the result of a new foreign accountability norm concerning the conditions under which natural resources are extracted. Secondly, it shows that the emergence of this norm is the result of strategic framing, in particular by moral entrepreneurs. International NGOs have successfully advocated the foreign accountability norm by placing it within already existing free market norms, instead of provoking open confrontation. Thirdly, in addition to the classical norm life cycle, the article shows that agency has also played a crucial role in the current phase of norm cascade. 'Fair business' entrepreneurs benefit from new markets for certified products, such as 'conflict free' phones, and their marketing enhances the norm cascade.